Characteristics and Response to Methylprednisolone and Prednisone Treatment of Optic Neuritic Patient at Sanglah General Hospital Denpasar - Dita-Rinjani, N. P.; Mas-Putrawati, A. A.; Putra-Manuaba, I. B. (BALI MEDICAL JOURNAL, 2012)
Objective: Treatment of optic neuritic as recommended by the Optic Neuritic Treatment Trial (ONTT) was intravenous methylprednisolon followed by oral prednisone. This study aims to describe characteristics and response to intravenous methylprednisolon followed by oral prednisone treatment of optic neuritic patient in Sanglah General Hospital Denpasar. Method: This report is an analytical cross sectional study. Data were collected retrospectively from medical report of optic neuritic patient who came to Sanglah General Hospital during a period of January 1st 2010 until December 31st 2011. Patient characteristics were analyzed with descriptive analyses and presented as frequency, percentage, mean and standar deviation. Visual acuity and contrast sensitivity improvement after intravenous methylprednisolon followed by oral prednisone treatment were statistically analyzed with Wilcoxon test Results: Optic neuritic were found in twenty-three patients (33 eyes), majority was in age group of 15-40 years (56.5%) with female predominance (65.2%) and unilateral involvement was 56.3%. Mean onset patient presented to the hospital was 21.7±2.21 days and the most common symptom was decreasing vision (87.9%). The majority of patient presented with papillitis (54.5%), totally color blindness found in 39.4% eyes, and the type of visual field defect at presentation was central scotoma (18.2%). All cases show lesion of optic nerve from visual evoked potential (VEP) examination and magnetic resonance imaging (MRI) shows normal results (39.1% patient). The mean of pretreatment logMAR visual acuity and contrast sensitivity were significant improve after treatment from 1.59±0.47 to 0.59±0.62 (p=0.0001) and 0.31±0.56 to 1.25±0.56 (p=0.0001), respectively. All cases in this study were idiopathic. Recurrence were seen in 2 eyes and none of patient had clinical features suggestive of multiple sclerosis. Conclusions: Visual acuity and contrast sensitivity improvement after intravenous methylprednisolon followed by oral prednisone treatment in this study is good, with lower rate of recurrence and none of cases associated with multiple sclerosis.